(untitled) (Researcher: A Research Journal of Culture and Society, 2021)
Nepal has entered into multiparty democracy in 1951. From begging to till dates of these seven decades, three decades were practiced party-less Panchayat system where political parties were outlawed. Within the remaining four decades Nepal has conducted seven national elections held in accordance to democratic norms and values. Many political parties fielded their candidates in these elections. They got various positions as per the cast of votes by Nepalese citizens. Results of elections show that Nepal has implemented the multiparty system. That was not the single or bi-party system. This article tries to analyze the participation of political parties in the elections and their position after the elections. It is based on reports published by the election commission after each election of Nepal. It analyzes only data of national elections. Nepali Congress (NC) a rightist party is a popular party of Nepal; results of elections proved it. Similarly, communists are also popular among Nepalese voters. They obtained higher votes in some national elections of Nepal. Other some rightist and leftist parties have also appeared in a significant position in the scenario of national politics of Nepal.